2020
DOI: 10.1101/2020.05.12.20095885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac Structural and Functional Characteristics in Patients with Coronavirus Disease 2019: A Serial Echocardiographic Study

Abstract: BACKGROUND: Increasing attention has been paid to cardiac involvement in patients with coronavirus disease 2019 ). Yet, scarce information is available regarding the morphological and functional features of cardiac impairments in these patients. METHODS:We conducted a prospective and serial echocardiographic study to investigate the structural and functional cardiac changes among COVID-19 patients admitted to the intensive care unit (ICU). From January 21 to April 8, 2020, a total of 51 ICU patients (31 critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Participants in our groups were well-matched for age, sex and comorbidities. The commonest echocardiogram abnormality noted in our study was TR, similar to ndings from another study (31), and under one third of our patients demonstrated RV dysfunction. The latter could be secondary to the acute respiratory distress syndrome seen in critically ill COVID-19 patients, which results in RV systolic dysfunction (8,32,33).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Participants in our groups were well-matched for age, sex and comorbidities. The commonest echocardiogram abnormality noted in our study was TR, similar to ndings from another study (31), and under one third of our patients demonstrated RV dysfunction. The latter could be secondary to the acute respiratory distress syndrome seen in critically ill COVID-19 patients, which results in RV systolic dysfunction (8,32,33).…”
Section: Discussionsupporting
confidence: 91%
“…Anecdotal evidence has demonstrated that elevation of PASP and then a sudden depreciation in COVID-19 fulminant myocarditis was likely linked to right heart functional decline secondary to sustained overload (43). In concordance with other studies, elevated PASP and right heart enlargement was signi cantly predictive of mortality (31). In fact, taking into consideration the crucial role of right heart function, the German Society of Cardiology concluded that optimum RV functioning was essential for COVID-19 patients' prognosis (44).…”
Section: Discussionmentioning
confidence: 58%
“…Four studies were excluded due to unavailability of the full-text. Finally, 56 papers ( [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ) entered into meta-analysis for primary outcomes (mortality and ICU admission) and 198 papers [ 16 , 18 , [21] , [22] , [23] , [24] , [25] , [26] ,…”
Section: Resultsmentioning
confidence: 99%